Antibacterial, antioxidant and total flavonoid of Adenostemma lavenia (L.) - ZEBUA, NILSYA FEBRIKA; FUJIKO, MUFLIHAH; DACHI, KANNE; NERDY, NERDY; SEPTAMA, ABDI WIRA (Universitas Syiah Kuala, 2024)
Adenostemma lavenia (L.) is one of the medicinal plants on Nias Island that is used to treat many symptoms including cough, fever and diarrhea. Empirical data of this plant suggests that these medicinal benefits can be attributed to its antibacterial and antioxidant properties, as well as the total flavonoids contained within it, but research on this is still limited. Adenostemma lavenia (L.) was extracted with ethanol, while the antibacterial properties were measured using the disc method. Antioxidant testing was conducted with the DPPH (1,1-diphenyl-2-2picrihydrazyl) inhibition method. Total flavonoids were assessed using a modified AlCl3 method with a quercetin standard. Antibacterial test results of Staphylococcus aureus, Klebsiela pneumoniae, Propionibacterium acnes, Escherichia coli, Salmonella typhi, Bacillus cereus and Shigella sonnei with mean inhibition were 8.76 0.44, 8.13 0.72, 8.77 0.45, 6.47 0.54, 7.77 0.60, 7.33 0.44, 12.06 0.60 respectively. IC50 was 59.844 3.36 ppm. Total flavonoids were 13.566 0.021 mcg/g. The results of the antibacterial test of the ethanolic extract of Adenostemma lavenia (L.) were classified as moderate. The antioxidant activity and total flavonoids were in the high category, which can be attributed to the capture of free radicals to overcome disease.